Effect on different heating time of ZnO/GO composite in semiconductor materials using hydrothermal method - Muhammad Firdaus Azmi (2024)
Effect on different heating time of ZnO/GO composite in semiconductor materials by Hydrothermal Methods. In this study, ZnO nanoparticles were integrated with GO sheets to enhance the material's electronic and structural properties. The hydrothermal synthesis method was employed to facilitate the controlled growth of ZnO on the GO surface under different heating (6 hours, 10 hours, 14 hours, 18 hours, 22 hours) at 180°C. The composites were characterized using various techniques, including X-ray diffraction (XRD). The impact of varied heating times on the structural and morphological features of the ZnO/GO composites was systematically assessed. Furthermore, the optical and electronic properties of the composites were investigated through UV-Visible spectroscopy. The observed variations in these properties were correlated with the heating time during the hydrothermal synthesis process. The findings of this study contribute to a comprehensive understanding of the synthesis-structure-property relationships in ZnO/GO composites, providing insights into the optimization of their performance for semiconductor applications. The made synthesis conditions explored in this research offer valuable information for designing semiconductor materials with enhanced characteristics, holding potential significance for applications in electronic devices and optoelectronic systems.